Effects of Alcohol and Cocaine in a Mutant Mouse Model of Predisposition to Post-Traumatic Stress Disorder - Paizanis, Eleni; Crotti, Michela; Petit, Anthony; Règue, Mathilde; Beray-Berthat, Virginie; Noble, Florence; Lanfumey, Laurence; Mongeau, Raymond (Frontiers in Pharmacology, 2020)
Comorbidity between drug abuse and post-traumatic stress disorder (PTSD), a trauma- related dysregulation of fear responses, is very high. While some drugs are known to increase fear and anxiety, there are only few data regarding interactions between voluntary drug consumption and fear memory. The spontaneous chronic consumption of either alcohol or cocaine under a 3-week free-choice progressive paradigm of alcohol (3/6/10 %) or cocaine (0.2/0.4/0.6 mg/mL), was assessed in VGV transgenic mice, having full 5-HT2C receptor editing and displaying PTSD-like behaviors. The consequences of these drug consumptions on the potentiated contextual and cued fear conditioning responses of VGV mice were assessed. The effects of drugs on hippocampal brain-derived neurotrophic factor (Bdnf) mRNA were measured as its expression was previously found to be decreased in VGV mice. Compared to WT mice, VGV mice tended to consume more alcohol at low and moderate concentrations, but not at high concentration. Alcohol reduced fear acquisition at the end of the learning sessions, and facilitated cue-fear extinction. Regarding cocaine, in contrast to WT mice, VGV mice did not increase their drug consumption along with increasing doses, an effect that might be related with enhanced drug stimuli discrimination via increased 5-HT2C receptors. Cocaine-intake VGV mice did not display the contextual fear generalization usually observed in control VGV mice. In addition, Bdnf expression was upregulated after either chronic alcohol or cocaine intake. Altogether, these results suggest that both chronic alcohol and cocaine voluntary oral consumptions can exert some therapeutic-like effects in a mutant model of PTSD predisposition.